Comparative Effectiveness of Combined Pharmacologic and Mechanical Thromboprophylaxis versus Either Method Alone in Major Orthopedic Surgery: A Systematic Review and Meta‐analysis. Issue 3 (11th February 2013) - Sobieraj, Diana M.; Coleman, Craig I.; Tongbram, Vanita; Chen, Wendy; Colby, Jennifer; Lee, Soyon; Kluger, Jeffrey; Makanji, Sagar; Ashaye, Ajibade; White, C. Michael
Abstract : Study Objective: To evaluate the comparative efficacy and safety of combination pharmacologic and mechanical venous thromboembolism (VTE) prophylaxis versus either method alone in major orthopedic surgery. Design: Systematic review with meta‐analysis of six randomized controlled trials. Patients: Patients undergoing total hip replacement, total knee replacement, or hip fracture surgery who received VTE prophylaxis. Measurements and Main Results: We conducted a systematic literature search of the MEDLINE, Cochrane Central Register of Controlled Trials, and Scopus databases (January 1980–July 2011) to identify trials that directly compared pharmacologic plus mechanical VTE prophylaxis to either strategy alone, evaluated United States Food and Drug Administration–approved agents, and reported rates of mortality, VTE, bleeding, and other adverse effects. Six trials were included, none of which were conducted in patients who had hip fracture surgery. The quality of each trial was evaluated, and the strength of evidence for each outcome was rated. No significant difference was found in the rate of pulmonary embolism or nonfatal pulmonary embolism when the combination of pharmacologic and mechanical prophylaxis was compared to pharmacologic prophylaxis alone, with low strength of evidence. The risk of deep vein thrombosis (DVT) was significantly decreased in the combination group (relative risk [RR] 0.48 [95% confidence interval (CI) 0.32–0.72]), with moderate strength of evidence, with benefits of combination therapy persisting in the total knee replacement subgroup (RR 0.41 [95% CI 0.25–0.68]). There was insufficient evidence to evaluate other final or intermediate outcomes or harms. In the comparison of combined pharmacologic and mechanical prophylaxis to mechanical prophylaxis alone, there was insufficient evidence to evaluate any final health outcomes or harms. There was no significant difference in the risk of proximal DVT when comparing combination prophylaxis to mechanical prophylaxis alone (RR 0.78 [95% CI 0.35–1.74]) based on low strength of evidence. Conclusions: The risk of DVT was decreased with the use of combination prophylaxis versus pharmacologic prophylaxis alone in patients undergoing total hip replacement or total knee replacement. However, due to primarily insufficient evidence for most outcomes evaluated, the balance of benefits to harms of combined pharmacologic and mechanical prophylaxis versus either strategy alone cannot be determined in patients undergoing major orthopedic surgery.